Extramedullary hematopoiesis masquerading as a cranial (clivus) tumor - Krause, John R. (Proc (Bayl Univ Med Cent), 2019)
Extramedullary hematopoiesis (EMH) is a well-known phenomenon occurring during fetal development. In the postfetal condition, EMH is commonly associated with hematologic conditions including chronic myeloproliferative or lymphoproliferative disorders, leukemias, and chronic and inherited anemias. We report an unusual location for EMH that masqueraded as a cranial tumor.